2017
DOI: 10.1101/103069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heritability enrichment of specifically expressed genes identifies disease-relevant tissues and cell types

Abstract: Genetics can provide a systematic approach to discovering the tissues and cell types relevant for a complex disease or trait. Identifying these tissues and cell types is critical for following up on non-coding allelic function, developing ex-vivo models, and identifying therapeutic targets. Here, we analyze gene expression data from several sources, including the GTEx and PsychENCODE consortia, together with genome-wide association study (GWAS) summary statistics for 48 diseases and traits with an average samp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
259
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(281 citation statements)
references
References 104 publications
20
259
2
Order By: Relevance
“…. Finally, at the trait level, we observed that CTS annotations 7,48 with significant CVE tend to have similar LFVE (or larger LFVE for brain-related annotations and traits; see below),…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…. Finally, at the trait level, we observed that CTS annotations 7,48 with significant CVE tend to have similar LFVE (or larger LFVE for brain-related annotations and traits; see below),…”
Section: Discussionmentioning
confidence: 74%
“…reflecting regulatory activity in a given cell type) with excess contributions to common variant architectures. For each of the 40 UK Biobank traits, we selected the subset of 396 CTS Roadmap annotations 7 with statistically significant common variant enrichment after conditioning on (non-CTS annotations in) the baseline-LD model 5,48 (see Online Methods). We selected a total of 637 trait-annotation pairs, with at least one CTS annotation for 36 of 40 traits (25 of 27 independent traits) (Table S9); the 637 CTS annotations contained 2.7% of common variants and 3.0% of low-frequency variants on average (Table S10).…”
Section: Cell-type-specific Annotations Dominate Both Low-frequency Amentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the eHi-C readouts to multiple sets of human genetic results selected due to the availability of large GWAS (Table S2). We evaluated the connection between Hi-C readouts and these GWAS using partitioned LD score regression 90,91 . In effect, we estimate the degree to which the SNPheritability of a trait is enriched in a set of genomic features (e.g., FIREs).…”
Section: Comparing Hi-c Readouts To Human Genetic Resultsmentioning
confidence: 99%